Narcisismo e o Processo de Morrer: A Potência do Encontro com o Outro - Nunes, Morgana (2024)
This article is part of a master's thesis that aimed to understand the possible narcissistic consequences of the subject with chronic illness and in palliative care. In this excerpt, we link the concept of narcissism, from the Freudian perspective, to the process of death and dying, especially regarding the power of the encounter with the other. Considering that in the construction of psychoanalytic thought, theory and practice frequently intersect, and that it is this "intersection" that allows metapsychological progress, the clinical recorded by the first author about her experience with patients in the process of terminality, in the context of palliative care. And, to give life and subtlety to the theme, we also use literature and poetry in this construction. The analysis of this material made it possible to visualize existing similarities between the baby's narcissistic constitution processes and the narcissistic reorganization of the one who dies, emphasizing the fundamental role of the other in the dying process. In terminality, this other can play the role of care, support and appointment of this new body that is presented, helping the patient to build new meanings for the lived experiences and also to think about the path to death.